The Influence Of Financial Technology Innovation On Micro Small Medium Msmes In Labuhan Batu - Yudi Prayoga; Bhakti Helvi Rambe; Maria Silaban (STIE AMKOP, 2023)
The purpose of this study was to find out how much knowledge about the influence of financial technology innovation on the development of small and medium enterprises in port of Batu. This study explains that the people in Batu Labuhan must be able to take advantage of financial technology (fintech), especially for MSMEs in Batu Labuhan because of financial technology (fintech), it is hoped that all regions, especially disadvantaged areas, will be able to advance and utilize their regional potential. Explanation of Sugiyono the Likert scale is used to measure the income and perceptions of a person or group of people about social events or phenomena. It can be concluded that the Likert scale is an alternative measurement that can be used to measure an event or social phenomenon which is then converted into numbers so that it is easy for researchers to conclude alternatives. The measurement model in this study consists of a reflective measurement model in which the financial technology variables, the development of small and medium enterprises and SMEs in Batu Labuhan are reflected. In Hair et al (2021) the reflective measurement model consists of loading > 0.70, composite reliability > 0.70 cronbach's alpha and average variance extracted and (AVE > 0.05) and evaluation of discriminant validity, namely Fornell and Lacker criteria and HTMT (heterotrait ratio) below 0.90 cross loading